Praktik jurnalisme data pada akun Tiktok @riaupos - Lestari, Nilam Ayu; Yesicha, Chelsy (Program Studi Ilmu Komunikasi UII, 2026)
This study aims to describe the data journalism practices on the TikTok account @riaupos and identify the challenges that arise in its implementation as a form of data journalism on social media in the era of media convergence. This study used a descriptive qualitative method with data collection techniques including interviews, documentation, and observation. The data obtained were analyzed using Paul Bradshaw's data journalism model and Henry Jenkins' media convergence theory. The research data was collected through observation and documentation of several short video uploads on the TikTok account @riaupos. The results show that the data journalism practices on the TikTok account @riaupos are implemented through data processing into short video content that combines visualization and narrative. Analysis of some of the content demonstrates the application of data journalism elements according to Paul Bradshaw. Challenges faced include difficulty in obtaining data, lengthy verification processes, and high workloads. Furthermore, the application of Henry Jenkins' media convergence theory is evident through multimedia integration, team collaboration, and cross-platform distribution.